Characterization of SR 121463A, a highly potent and selective, orally active vasopressin V2 receptor antagonist. - C Serradeil-Le Gal; C Lacour; G Valette; G Garcia; L Foulon; G Galindo; L Bankir; B Pouzet; G Guillon; C Barberis; D Chicot; S Jard; et al. (The Journal of Clinical Investigation, 1996)
SR 121463A, a potent and selective, orally active, nonpeptide vasopressin V2 receptor antagonist, has been characterized in several in vitro and in vivo models. This compound displayed highly competitive and selective affinity for V2 receptors in rat, bovine and human kidney (0.6 < or = Ki [nM] < or = 4.1). In this latter preparation, SR 121463A potently antagonized arginine vasopressin (AVP)-stimulated adenylyl cyclase activity (Ki = 0.26+/-0.04 nM) without any intrinsic agonistic effect. In autoradiographic experiments performed in rat kidney sections, SR 121463A displaced [3H]AVP labeling especially in the medullo-papillary region and confirmed that it is a suitable tool for mapping V2 receptors. In comparison, the nonpeptide V2 antagonist, OPC-31260, showed much lower affinity for animal and human renal V2 receptors and lower efficacy to inhibit vasopressin-stimulated adenylyl cyclase (Ki in the 10 nanomolar range). Moreover, OPC-31260 exhibited a poor V2 selectivity profile and can be considered as a V2/V1a ligand. In normally hydrated conscious rats, SR 121463A induced powerful aquaresis after intravenous (0.003-0.3 mg/kg) or oral (0.03-10 mg/kg) administration. The effect was dose-dependent and lasted about 6 hours at the dose of 3 mg/kg p.o. OPC-31260 had a similar aquaretic profile but with markedly lower oral efficacy. The action of SR 121463A was purely aquaretic with no changes in urine Na+ and K+ excretions unlike that of known diuretic agents such as furosemide or hydrochlorothiazide. In addition, no antidiuretic properties have been detected with SR 121463A in vasopressin-deficient Brattleboro rats. Thus, SR 121463A is the most potent and selective, orally active V2 antagonist yet described and could be a powerful tool for exploring V2 receptors and the therapeutical usefulness of V2 blocker aquaretic agents in water-retaining diseases.